Primitive, now: The clinical use of a word - Balzaretti, Alessandro (Rivista di Psicologia Clinica - Open Access, 2025)
Clinicians and researchers often use the term “primitive” in reference to emotions and mental states. The widespread use of this term in literature, not only from psychoanalytic tradition, and in professional practice, forces it to explain its meaning. From a cultural psychological background, sensitive to psychoanalytical literature, six possible meanings of the term will therefore be proposed. The aim is to mobilize the self-reflection capacity of the clinician and the educator, so that the relationship does not freeze in the polarity of nature-culture. Finally, it is hypothesized that this term, when referring to the basic needs of some categories of patients, makes space for the ethics and the responsibility, both entirely human, of psychological intervention.